Research Progress of Unpowered Exoskeleton Assist Robot - Shen Jingyu; Zhang Shimin; Chen Chong; Xu Zhiyao (Jixie chuandong)
Unpowered exoskeleton assist robots have the advantages of no energy consumption， low cost and convenient use， which can be widely used in industry manufacture， medical rehabilitation and other fields. The definition and classification are expounded systematically and the principles are introduced. The kinematic diagram of typical domestic and foreign unpowered exoskeleton assist robot is drawn and the corresponding structure principle is briefly described. Finally， the shortcomings， key technologies that need to be broken through are summarized based on the survey results. It should be helpful for those researchers devoted to unpowered exoskeleton support robots.